Soil eutrophication and tree community in patches of an agricultural landscape - Uzêda, Mariella Camardelli; Fidalgo, Elaine Cristina Cardoso; Moreira, Renato Valadares de Sousa; Fontana, Ademir; Donagemma, Guilherme Kangussu (Pesquisa Agropecuaria Brasileira, 2016)
This objective of this work was to evaluate the effect of soil eutrophication in remaining patches of native vegetation on the floristic community of trees in agricultural landscapes. Eight sites of arboreal vegetation were sampled in the Atlantic Forest, in state of Rio de Janeiro, Brazil, in pairs formed according to land use in their boundary – intensive (UI) or extensive (UE) –, and with different sizes: two small sites, with about 10 ha; two medium-sized ones, with 30 ha; two large ones, with 100 ha; and two sites located within a continuous forest area. A set of biotic and soil parameters, besides landscape metrics, was surveyed and analyzed considering two hypotheses: H01, soil fertility is changed in forest remnants next to areas of intensive agricultural use; and H02, soil eutrophication in forest remnants next to areas of intensive agricultural use changes the composition of its tree community. Calcium contents were about seven times higher in sites next to UI areas, in comparison with those next to UE areas. Phosphorous contents were 1.5 to 2.5 times higher in the small and medium-sized patches next to UI areas. The ordering analysis showed that P, K, Ca, diffuse light, canopy opening, area/perimeter ratio, and patch isolation account for 59% of the tree community composition.